Signal-to-noise ratio improvement of the signal immersed in the strong background noise using a bistable circuit with tunable potential-well depth. (1st September 2022) - Yang, Kai; Tong, Weihao; Huang, Zhou; Qiu, Tian; Lai, Zhihui
Abstract: Fault detection is one of the primary tasks in aerospace engineering. A clean target signal is required to improve the detection quality. This paper introduces a bistable nonlinear circuit with tunable potential-well depth (TPWD) to improve the signal-to-noise ratio (SNR) of the signal immersed in strong noise background. The TPWD bistable circuit utilizes the tunable bifurcation feature of the nonlinear dynamics to extract the target signal under different noise conditions. The theory of the circuit is first presented. Then, under noise circumstances, the fidelity of the mathematical model of the circuit is validated through experiments. Results show that owing to the TPWD bistable circuit, the target signal can be extracted and the SNR of the target signal is enhanced under different noise conditions. In some conditions, the adjustment of potential-well depth can induce different bifurcation features of the circuit, leading to the SNR enhancement. Finally, to demonstrate the feasibility of the TPWD bistable circuit in incipient fault diagnosis, it is employed to detect a shaft bending fault. Results show that the TPWD bistable circuit with the appropriate specification can significantly enhance the SNR of the target vibration signal of the shaft which is immersed in strong background noise. This is beneficial to the detection of the symptom of the bent shaft. Hence, the study proves that the proposed circuit can show a capability in real-time fault diagnosis without complicated programmable acquisition system.